2016
DOI: 10.1620/tjem.240.251
|View full text |Cite
|
Sign up to set email alerts
|

Early RAAS Blockade Exerts Renoprotective Effects in Autosomal Recessive Alport Syndrome

Abstract: Alport syndrome is a progressive renal disease caused by mutations in COL4A3, COL4A4, and COL4A5 genes that encode collagen type IV alpha 3, alpha 4, and alpha 5 chains, respectively. Because of abnormal collagen chain, glomerular basement membrane becomes fragile and most of the patients progress to end-stage renal disease in early adulthood. COL4A5 mutation causes X-linked form of Alport syndrome, and two mutations in either COL4A3 or COL4A4 causes an autosomal recessive Alport syndrome. Recently, renin-angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Therefore, this analysis finally included 26 eligible articles with 148 patients (Figure 1) [7,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. The respective characteristics of included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this analysis finally included 26 eligible articles with 148 patients (Figure 1) [7,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. The respective characteristics of included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that, for the treatment of AS, renin–angiotensin–aldosterone system (RAAS) blockade should be initiated before renal function is impaired [ 8 ]. Gross et al demonstrated that the best therapeutic effect was obtained in AS patients when the treatment was initiated before the development of proteinuria [ 9 ].…”
Section: Discussionmentioning
confidence: 99%